Extracellular heme:DNA complexes promote oxidative stress and inflammation during lupus-associated hemolysis - Lubica Janovicova; Monika Janikova; Michal Pastorek; Eva Csizmadia; Cherith Yoder; Alexandra Lesayova; Liam Geyer; Vasileios C. Kyttaris; George C. Tsokos; Peter Celec; Barbara Wegiel (Proceedings of the National Academy of Sciences, 2026)
Hemolysis is associated with the release of damage-associated molecular patterns, including free heme and extracellular DNA (ecDNA). Using several mouse models of bleeding anemia and hemolysis, we demonstrate a significant increase in plasma ecDNA, independent of neutrophil extracellular trap formation. This ecDNA forms G-quadruplex (G4) structures, which we detected in both mice and patients with systemic lupus erythematosus. Catalytic complexes (DNAzymes) formed by G4 ecDNA and heme drive oxidative stress, tissue injury, and inflammation. In anemic mice lacking deoxyribonuclease 1L3 ( DNase1l3 −/− ), we found elevated polynucleosomal ecDNA in the plasma, reduced expression of the heme-degrading enzyme heme oxygenase-1 in macrophages, but also increased plasma creatinine, renal iron accumulation, and complement C3 deposition along elevated apoptosis and DNA damage. ecDNA isolated from these mice also triggered toll-like receptor 9-dependent inflammatory responses in vitro and in vivo. In summary, these findings suggest that concurrent release of heme and ecDNA during hemolysis promotes inflammation and tissue damage, contributing to lupus pathogenesis.